Hubungan Kompetensi Kepribadian Guru PAI Dengan Hasil Belajar Siswa Pada Mata Pelajaran Akidah Akhlak - Raito, Raito; Rahman, Eep Syaepul (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
The role of teachers in education is very important and their quality must be considered. A teacher is someone who provides education to students so that the goals of education can be achieved. However, teachers must also have good and mature competencies so that all learning processes are as expected. One of them is having good personality competence, because when a teacher has good personality competence, this will encourage students to improve their learning outcomes because they make the teacher an example in their life. This research aims to determine the relationship between PAI Teacher Competency and Student Learning Outcomes in the Akidah Akhlak subject in class VIII MTs AL-Ma'arif Kadungora Garut. Apart from that, this research aims to determine the extent to which the teacher's role in the Akidah Akhlak subject affects their personality competence. So that a percentage can be obtained to what extent the teacher' personality competence influences student learning outcomes. The method used in this research uses the Correlative Quantitative Descriptive Method, so that a relationship will be obtained between the Independent Variable (personality competency) and the Dependent Variable (learning outcomes). The subjects in this research are class VIII students at MTs Al-Ma'arif Kadungora Garut, namely as many as 40 people. The results of his study indicate that the statistical tests, there is a relationship between Islamic Education Teacher Competency and Student Learning Outcomes in the Akidah Akhlak subject in class VIII MTs AL-Ma'arif Kadungora Garut of 63%, while other factors that influence student learning outcomes are 37% but were not examined in the research This. These are the findings from the results of this study. Keywords: Personality Competency, Student Learning Outcomes, Akidah Akhlak Learning.